North Star Ambulatory Assessment changes in ambulant Duchenne boys amenable to skip exons 44, 45, 51, and 53: A 3 year follow up. - Giorgia Coratti (Public Library of Science (PLoS), 2021)
Introduction The aim of this study was to report 36-month longitudinal changes using the North Star Ambulatory Assessment (NSAA) in ambulant patients affected by Duchenne muscular dystrophy amenable to skip exons 44, 45, 51 or 53. Materials and methods We included 101 patients, 34 had deletions amenable to skip exon 44, 25 exon 45, 19 exon 51, and 28 exon 53, not recruited in any ongoing clinical trials. Five patients were counted to skip exon 51 and 53 since they had a single deletion of exon 52. Results The difference between subgroups (skip 44, 45, 51 and 53) was significant at 12 (p = 0.043), 24 (p = 0.005) and 36 months (p≤0.001). Discussion Mutations amenable to skip exons 53 and 51 had lower baseline values and more negative changes than the other subgroups while those amenable to skip exon 44 had higher scores both at baseline and at follow up. Conclusion Our results confirm different progression of disease in subgroups of patients with deletions amenable to skip different exons. This information is relevant as current long term clinical trials are using the NSAA in these subgroups of mutations.